The challenges of defence spending in Europe - Daniel Fiott (Intereconomics, 2024)
After decades of relative peace and security, Europe is faced with a conflict on its doorstep that threatens to upend the recent stability and shift geopolitical order. Russia's war of aggression in Ukraine has forced Europe to confront its shortcomings with regard to providing its own security and to reconsider its reliance on the United States, which may be - under a potential Trump administration - much less supportive. This Forum focuses on what needs to be done now to address Europe's security concerns and guarantee stability for the foreseeable future. Is meeting NATO spending targets enough to support European defence? What would it take to make Europe more self-sufficient? How does Europe protect itself against malicious cyberattacks? And what role do women specifically play in supporting defence efforts and future reconstruction in Ukraine?
Keywords: O33; F50; N44; H50; H56; 330